STUDY ON LEAF QUALITY OF MULBERRY (MORUS ALBA. L.; VAR. S-1635) THROUGH REARING AND REELING OBTAINED FROM ORGANIC FARMING APPROACH - CHOWDHURY, P.K.; SETUA, G.C.; KAR, N.B.; GHOSH, A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
An experiment was conducted during 2009-2010 at the Central Sericultural Research and Training Institute, Berhampore (West Bengal) on bioassay with multi x multi N (M) x M12W) silkworm (Bombyx mori L.) hybrid rearing in July and September during unfavourable season and with multix biN X (SK6 X SK7) hybrid in November and February during favourable season along with reeling study to assess the quality of leaf of high yielding and popular mulberry variety S1635 at 60cm x 60cm spacing, obtained through seven different treatment combinations /packages of which 4 were of organic package, l established INM package, 1 without any nutrient (absolute control) as well as I recommended package (control), under five crop schedule per year, cultivated under irrigated, Gangetic alluvial soil conditions. The leaves obtained from seven treatment combinations were fed to silkworms. The rearing result of July, '09 indicated that the effect of the treatments were found significant on weight of 10 matured larvae, wt. of cocoon /10000 larvae, single cocoon weight and single shell weight, whereas only weight of 10 matured larvae was found significant in September, '09. The rearing result of November, '09 indicated that the effect of the treatments were found significant on weight of 10 matured larvae, wt. of cocoons/10000 An experiment was conducted during 2009-2010 at the Central Sericultural Research and Training Institute, Berhampore (West Bengal) on bioassay with multi x multi N (M) x M12W) silkworm (Bombyx mori L.) hybrid rearing in July and September during unfavourable season and with multix biN X (SK6 X SK7) hybrid in November and February during favourable season along with reeling study to assess the quality of leaf of high yielding and popular mulberry variety S1635 at 60cm x 60cm spacing, obtained through seven different treatment combinations /packages of which 4 were of organic package, l established INM package, 1 without any nutrient (absolute control) as well as I recommended package (control), under five crop schedule per year, cultivated under irrigated, Gangetic alluvial soil conditions. The leaves obtained from seven treatment combinations were fed to silkworms. The rearing result of July, '09 indicated that the effect of the treatments were found significant on weight of 10 matured larvae, wt. of cocoon /10000 larvae, single cocoon weight and single shell weight, whereas only weight of 10 matured larvae was found significant in September, '09. The rearing result of November, '09 indicated that the effect of the treatments were found significant on weight of 10 matured larvae, wt. of cocoons/10000 larvae, single cocoon weight and reelability (%), whereas only weight of 10 matured larvae, wt. of cocoons/10000 larvae, single cocoon weight, single shell weight, SR%, and filament length were found significant in February, 2010. The overall result of four rearing (bio-assay) revealed that T3 (30mt vermicompost ie. VC "ha/year) performed almost similar or better in respect of wt. of 10 matured larvae, wt. of cocoons/10000 larvae, SCW, SSW, SR% and almost similar filament length with T2 recommended package or control i.e. 20mt FYM/ha/year + 336N: 180P: 112K kg/ha/year) followed by T7 (INM package i.e. 15mt VC/ha/year + AMF-inoculated saplings (Glomus mosseae) + Azotobacter chroococcum (a) 20kg/ha/year + 50% rec. dose of N, P and K (168N: 90P. 56K kg/ha/year) under unfavorable season. In case of favourable season, T3 also performed well in wt. of 10 matured larvae (2" highest), wt. of cocoons/10000 larvae, SCW, SSW and ERR (%) followed by T2 and T7. - Before above study, an experiment was also done on mulberry for 3 years and the result indicated that the organic package i.e. T3 (30mt VC/ha/year) was found to be better and potential over T2 (recommended package) from third year onwards with 6.41% more leaf yield (45.313.80kg/ha/year), improved leaf quality, maximum net profit (Rs 22696.47/ha/year) along with better cost-benefit ratio 1:1.33 in spite of marginally higher expenditure (Rs 67931.13/ha/year) followed by T7 i.e. the integrated nutrient management package 15mt VC/ha/year+ fungal (AMF) and bacterial (AZB) biofertilizers + 50% rec. dose of N, P and K (168N: 90P:56K kg/ha/year) which contributed almost similar performances in respect of leaf yield and quality with recommended package. The result also indicated that the quantity and quality of leaf was improved slowly and became similar or more after 2 years of continuous application of vermicompost (1.5%N content) alone (T3) (a 30mt/ha/year in 5 equal split doses and performed overall promising as well as economic due to improvement in soil nutrient status, soil microbial population, growth attributing characters, almost similar or more sustainable leaf yield, marginally better leaf quality and benefit-cost ratio.